Growth performance of Nile Tilapia (Oreochromis niloticus) fingerlings fed with water spinach (Ipomoea aquatica) diets - Chepkirui M; Orina PS; Opiyo M; Muendo P; Mbogo K; Omondi R (Annals of Marine Science - Peertechz Publications, 2022)
Nile tilapia (Oreochromis niloticus) are herbivores with longer coiled intestines compared to carnivores; mouth characteristics necessary for plant shredding. Hence, several studies have been conducted to replace feed ingredients in the diet of Nile tilapia considering the increasing cost. In this study, Water spinach (Ipomoea aquatica) was evaluated as a potential feed ingredient for Nile tilapia. A six months feeding trial was conducted to assess the effects of water spinach fish feed composition on the performance of Nile tilapia fingerlings. Five diets were formulated containing 0% (control diet), 5%, 10%, 15% and 20% water spinach composition. Each treatment was carried out in triplicate using 30 Nile tilapia juveniles per replicate with an initial mean weight of 2±1g. The fish were fed at 5% body weight twice per day. Water quality monitoring was done every morning before feeding. There was no significant (p > 0.05) variation in water quality parameters between all the treatments. The best growth performance was recorded from a fish-fed 5% diet (180.49±0.83 g), while fish fed with a 20% diet had poor growth performance (128.98± 0.80g). The highest SGR was obtained in fish fed with a 5% diet (1.34±0.05) while the lowest was obtained in fish fed with a 20% diet (1.09±0.05). Except for SGR, WG, FL, and FW, there was no significant difference (P>0.05) in other growth parameters of all the treatments. Final weight had a significant difference as determined by One-Way ANOVA (F (4,316) =6.363, P=0.00) between 15% and 20% water spinach composition compared to 5% water spinach composition.  Therefore, 5% water spinach composition had the best growth performance.